Analisis Perhitungan Harga Pokok Produksi Pada Catering Dapoer Laziid (Pendekatan Variabel Costing) - Shalvira Siregar, Annisa; Meliza, Juli (Fakultas Ekonomi Universitas Gresik, 2023)
Catering Dapoer Laziid is a catering company that makes food for everything from daily meal catering to catering for large parties and events.Catering Dapoer Laziid handles a lot of orders, so it needs to break down production costs in detail.Medan City's Medan Johor neighborhood is home to Dapoer Laziid Catering. The data research technique in this study is a qualitative research method. Dapoer Laziid Catering may be able to assist MSMEs in calculating production costs after conducting research and analyzing how it calculated the cost of production using the variable costing method. Production costs and non-production costs, also known as fixed costs or factor costs, are distinguished using the variable costing method. A number of micro, small, and medium-sized businesses (MSMEs) have not included marketing and electricity costs in their production costs. Even though they are not included in the direct costs of production for the catering process at Dapoer Laziid, these costs also include expenses incurred. Due to this, the selling price of Dapoer Laziid's catering calculations and variable costing differed. The production cost incurred by Dapoer Laziid Catering under the variable costing method is higher, at Rp, as shown in the table above. 15,457 more than the Rp cost of production that was generated by Dapoer Laziid Catering employing the variable costing approach. 12,510, with a variance in Rp production costs. 2.947.When computing the expense of creation, contrasts in the worth of production line above costs bring about the distinction. This is because the variable costing method makes it easy to define the costs of raw materials, labor, and factory overhead